Hubungan Terapi Senam Yoga terhadap Hipertensi pada Lansia - Setiana Andarwulan (Jurnal Kebidanan Harapan Ibu Pekalongan, 2021)
Hypertension is a degenerative disease. This disease is usually suffered by the elderly. The method of treatment taken is through the use of drug consumption [lowering blood pressure, but taking long-term drugs can have a chemical effect in the body, so the use of drugs made from natural ingredients becomes one of the drugs in reducing blood pressure. In addition, yoga can also be used to lower blood pressure. By following exercise regularly. The purpose of this study was to determine the relationship between blood pressure and yoga exercises. The method used in this research is pre-experimental, with a population of 30 respondents, through the sampling technique, namely total sampling. The result of this research is that there is a difference between the correlation test of yoga exercise and blood pressure through the chi square test, the Asymp value is obtained. Sig. (2-sided) 0.025. There is a significant difference between blood pressure before and after doing yoga exercises.